Streamlined fabrication of hybrid lipid bilayer membranes on titanium oxide surfaces: a comparison of one- and two-tail SAM molecules - Sut, Tun Naw (2022)
There is broad interest in fabricating cell-membrane-mimicking, hybrid lipid bilayer (HLB) coatings on titanium oxide surfaces for medical implant and drug delivery applications. However, existing fabrication strategies are complex, and there is an outstanding need to develop a streamlined method that can be performed quickly at room temperature. Towards this goal, herein, we characterized the room-temperature deposition kinetics and adlayer properties of one- and two-tail phosphonic acid-functionalized molecules on titanium oxide surfaces in various solvent systems and identified optimal conditions to prepare self-assembled monolayers (SAMs), upon which HLBs could be formed in select cases. Among the molecular candidates, we identified a two-tail molecule that formed a rigidly attached SAM to enable HLB fabrication via vesicle fusion for membrane-based biosensing applications. By contrast, vesicles adsorbed but did not rupture on SAMs composed of one-tail molecules. Our findings support that two-tail phosphonic acid SAMs offer superior capabilities for rapid HLB coating fabrication at room temperature, and these streamlined capabilities could be useful to prepare durable lipid bilayer coatings on titanium-based materials.